Endoscopic removal of Impacted Intentionally ingested stone in Esophagus. - Shrestha, Ramila; Rajbhandari, Sabin; Kafle, Roshan; Shrestha, Milan; Shrestha, Dinesh (Bangladesh Journal of Medicine, 2024)
Intentional foreign body ingestion is commonly seen in patients with psychiatric illness and prisoners.It accounts for approximately 4% of urgent endoscopic procedures. Such intentional ingestion of foreign bodies are rare in conscious and healthy people.The majority of foreignbodies ingestion are accidental.Esophageal injury depends upon location and types of foreign body.It can cause problems such as difficulty in swallowing,excessive drooling,coughing,chest discomfort,vomiting of blood and respiratory problems.In our case, we used flexible endoscope with Dormia basket to remove intentionally ingested and then impacted stone in mid esophagus of a psychiatric patient. Bangladesh J Medicine 2024; 35: 211-213